Regional Specialization and the Supply of Wheat in the United States, 1867-1914: A Reply - Fisher, Franklin M.; Temin, Peter (The Review of Economics and Statistics, 1974)
Franklin M. Fisher, Peter Temin, Regional Specialization and the Supply of Wheat in the United States, 1867-1914: A Reply, The Review of Economics and Statistics, Vol. 56, No. 1 (Feb., 1974), pp. 114-115